Antibiotic‐induced effects on scaling relationships and on plant element contents in herbs and grasses. Issue 13 (2nd June 2018) - Minden, Vanessa; Schnetger, Bernhard; Pufal, Gesine; Leonhardt, Sara D.
Abstract: Plant performance is correlated with element concentrations in plant tissue, which may be impacted by adverse chemical soil conditions. Antibiotics of veterinary origin can adversely affect plant performance. They are released to agricultural fields via grazing animals or manure, taken up by plants and may be stored, transformed or sequestered by plant metabolic processes. We studied the potential effects of three antibiotics (penicillin, sulfadiazine, and tetracycline) on plant element contents (macro‐ and microelements). Plant species included two herb species ( Brassica napus and Capsella bursa‐pastoris ) and two grass species ( Triticum aestivum and Apera spica‐venti ), representing two crop species and two noncrop species commonly found in field margins, respectively. Antibiotic concentrations were chosen as to reflect in vivo situations, that is, relatively low concentrations similar to those detected in soils. In a greenhouse experiment, plants were raised in soil spiked with antibiotics. After harvest, macro‐ and microelements in plant leaves, stems, and roots were determined (mg/g). Results indicate that antibiotics can affect element contents in plants. Penicillin exerted the greatest effect both on element contents and on scaling relationships of elements between plant organs. Roots responded strongest to antibiotics compared to stems and leaves. We conclude that antibiotics in the soil, even in low concentrations, lead to low‐element homeostasis, altering the scaling relationships between roots and other plant organs, which may affect metabolic processes and ultimately the performance of a plant. Abstract : Antibiotics in the environment have been recognized as a serious threat to nontarget organisms as well as entire ecosystems. So far, knowledge is lacking on the effects of antibiotics on plant element contents. Our results indicate that antibiotics can affect element contents in plants and alter the scaling relationships between roots and other plant organs, which may affect metabolic processes and ultimately the performance of a plant.